The image construction of Loro Blonyo craft in global market through packaging design that reflect local image / Nanang Yuliantoa...[et.al] - Yuliantoa, Nanang; Tri Sulistyoa, Edy; Subiyantoroa, Slamet; Sigi Prameswaria, Nadia (2016)
Along with the globalization of the economy, sculpture craft products “Loro Blonyo” from Bobung, Patuk, Gunung Kidul in Yogyakarta are to meet the demand of consumers in the global market. Till now the demand of the consumer tend to product imagery that enhance the prestige of the consumer, therefore producers should realize in order to face these challenges. On approach to respond to these challenges is to develop the product packaging of “Loro Blonyo” sculpture that reflect the local culture to answer the exigency of the consumer. Choosing packing that reflect the local culture is expected to introduce the local values to the global stage.